Efficacy of sequential application of herbicide mixture for management of multiple herbicide resistant in Phalaris minor in wheat (Triticum aestivum) - KUMAR, SUSHIL; DADARWAL, R S; MAL, TODAR; AKSHIT; DEVI, PRIYANKA; KUMARI, ANNU; CHAHAL, GOURAV (The Indian Journal of Agricultural Sciences, 2024)
The emergence of multiple herbicide resistance in Phalaris minor is a major threat to wheat (Triticum aestivum L.) production in north-western Indo-Gangetic Plains of India. The present study was carried out during winter (rabi) seasons of 2020–21 and 2021–22 at research farm of Chaudhary Charan Singh Haryana Agricultural University, Hisar, Haryana for management of herbicide resistance in Phalaris minor Retz. in wheat using pre and post-emergence herbicide mixtures with different mode of action. The experiment was laid out in randomized block design (RBD) with 15 treatments, replicated thrice. Sequential application of flumioxazin 125 g/ha with pendimethalin (tank mix) 1500 g/ha fb clodinafop + metribuzin 174 g/ha resulted in significantly lowest weed density, dry matter of P. minor and broad-leaf weeds, and it was statistically comparable to application of flumioxazin alone or as mixture with pendimethalin as pre-emergence; pyraxosulfone + pendimethalin 127.5 + 1500 g/ha fb PoE (post-emergence) application of either mesosulfuron + iodosulfuron 14.4 g/ha; sulfosulfuron + metsulfuron, pinoxaden + metsulfuron 50 + 4 g/ha, clodinafop + metribuzin 174 g/ha, respectively. Phytotoxicity of flumioxazin was observed on wheat after 2–3 days of 1st irrigation i.e. 25 DAS (days after sowing). Application of pyroxasulfone + pendimethalin pre fb PoE mesosulfuron + iodosulfuron resulted in significantly higher grain yield (5847 and 5369 kg/ha, during 2021 and 2022, respectively) as compared to other herbicides.